If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(f + 2) = 2 + -1f Reorder the terms: 3(2 + f) = 2 + -1f (2 * 3 + f * 3) = 2 + -1f (6 + 3f) = 2 + -1f Solving 6 + 3f = 2 + -1f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add 'f' to each side of the equation. 6 + 3f + f = 2 + -1f + f Combine like terms: 3f + f = 4f 6 + 4f = 2 + -1f + f Combine like terms: -1f + f = 0 6 + 4f = 2 + 0 6 + 4f = 2 Add '-6' to each side of the equation. 6 + -6 + 4f = 2 + -6 Combine like terms: 6 + -6 = 0 0 + 4f = 2 + -6 4f = 2 + -6 Combine like terms: 2 + -6 = -4 4f = -4 Divide each side by '4'. f = -1 Simplifying f = -1
| 7x-98=4x-11 | | 3x-4=3(x-3) | | 7x+8=-28+4x | | 2a+10=32 | | 70-7x=2x+20 | | 88x-2x^2=0 | | 151-4x=32x+23 | | 7x-4=4x+29 | | 5x-5=45 | | 35p-12=5p+89 | | 7x^2+3x=8x | | 7(6x-5)=42x-35 | | x=x+2-2 | | 3x+4y=-5 | | 7a^4+6a^2-13= | | 3x+89=x(-2)x | | -98-10x=9x+16 | | -3-4d=13 | | .05(3t+8)=.15(t+5)-.35 | | (5x^2y+4xy^4)-(3x^2y-2xy^4)= | | -4+5x=1 | | 4x-58=158 | | (y+1)=(4y-5) | | x^2=48x+49 | | 2x-75=81 | | 4x-70=174 | | 2x-88=248 | | (w+3)+(3w-5)=180 | | 2x-17=31 | | 3x-46=59 | | 5x+28=98 | | 9x+19=100 |